Academic Publishing and «Predatory» Journals - Strielkowski, W.; Gryshova, I. (Наука та інновації, 2018)
Introduction. Publications in prestigious academic journals have a significant impact on the institutional rankings and help researchers to get grants. Problem Statement. Nevertheless, the issue of «where» to publish became more important than «what» to publish. The academic race for the higher number of publications led to debates about the phenomenon of the so-called «predatory» journals that publish scientific «rubbish» for money without proper peer review. Purpose. The purpose is to reveal the essence of «predatory» journals and to prove the necessity of indexation as an effective tool for assessing the quality of scientific publications. Materials and Methods. The ratings of scientific journals and publications in academic journals and «predatory» journals have been compared. Results. The Czech Republic is one of the countries that seem to be particularly obsessed with the issue of «predatory» journals making a storm in a teacup. According to some estimates, between 2009 and 2013, several Czech universities made around 2 million USD from their researchers their papers and monographs in «predatory» publishing outlets. The case of «predatory» journals was used by some less-productive institutes of the Czech Academy of Sciences to question the system of world's established academic metrics such as Scopus and Web of Science. Conclusions. All this is possible because currently there are many controversial lists and registries of «predatory» journals, which often contradict each other. However, it appears that indexation of academic journals in Scopus and Web of Science databases is more relevant for their academic worthiness than classifying them in accordance to a plethora of various amateurish lists and blogs.